Creativity amongst Children with Special Needs (CWSN): Tapping from School Teachers’ Experiences - Kumari, Archana; Sharma, Yukti (INDIAN EDUCATIONAL REVIEW, 2018)
The present paper focuses on exploring school teachers’ perceptions (N=20) about creative potentialities of CWSN by tapping on their experiences. The paper attempts to deconstruct the concept of creativity so that it can be understood in the context of children with special needs. By quoting experiences of teachers, the paper tries to understand and explore creative manifestations amongst CWSN as perceived by them. The findings indicated that the teachers who have direct interactions with CWSN possess positive inclination towards their creative potentialities as compared to others who do not engage with CWSN on a regular basis. The need of various pre-service and in-service programme which help teachers to equip themselves for nurturing the CWSN in their class was also voiced by the teachers during the discussions. The paper concludes by drawing out implications for school education as well as teacher education specifically focusing on the need for developing an inclusive pedagogy that focuses on needs of children arising by virtue of both their abilities as well as impairments.